2006
DOI: 10.1016/j.cub.2006.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Orchestration of the Hepatic Proteome

Abstract: Circadian rhythms are essential to health. Their disruption is associated with metabolic diseases in experimental animals and man. Local metabolic rhythms represent an output of tissue-based circadian clocks. Attempts to define how local metabolism is temporally coordinated have focused on gene expression by defining extensive and divergent "circadian transcriptomes" involving 5%-10% of genes assayed. These analyses are inevitably incomplete, not least because metabolic coordination depends ultimately upon tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
456
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 500 publications
(490 citation statements)
references
References 31 publications
(48 reference statements)
28
456
2
4
Order By: Relevance
“…As suggested by genome-wide transcription profiling experiments (Hughes et al 2009 and references therein) and proteomics studies (Reddy et al 2006), the temporal orchestration of metabolism is probably the major purpose of circadian gene expression in the liver and other metabolic organs, such as adipose tissues (Gimble et al 2011) and muscle (Lefta et al 2011). We wish to emphasize that circadian clocks do not work in isolation, but in tight cooperation with acute regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…As suggested by genome-wide transcription profiling experiments (Hughes et al 2009 and references therein) and proteomics studies (Reddy et al 2006), the temporal orchestration of metabolism is probably the major purpose of circadian gene expression in the liver and other metabolic organs, such as adipose tissues (Gimble et al 2011) and muscle (Lefta et al 2011). We wish to emphasize that circadian clocks do not work in isolation, but in tight cooperation with acute regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…Retinal cells are heterogeneous, and cell-type focused analysis including immunohistochemistry is required for understanding physiological roles of oscillating proteins. Recently, Reddy et al [55] reported a circadian proteomic analysis of the mouse liver, in which up to 20% of expressed protein spots showed circadian rhythmicity. The relative abundance of the rhythmic spots derived from the liver proteins may be caused by the effect of nighttime-specific feeding behavior because the liver is the central organ of food metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, analysis of the mammalian cycling proteome revealed that the proportion of cycling cytosolic proteins is rather higher than that found in microarray studies, and that many of the cycling proteins show a constant abundance at the level of the mature transcript (Reddy et al 2006). This discrepancy indicates that posttranscriptional and posttranslational mechanisms (largely unknown) are important components of circadian rhythmicity.…”
Section: Circadian Clocks: Posttranscriptional and Translational Regumentioning
confidence: 87%